2022
DOI: 10.21037/tcr-22-1438
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and clinical characteristics associated with never-smoking status in patients with lung cancer: findings from a large integrated health system

Abstract: Background: Evidence is limited characterizing sociodemographically diverse patient populations with lung cancer in relation to smoking status.Methods: In a cross-sectional analysis of adults diagnosed with lung cancer at ages ≥30 years from 2007-2018 within an integrated healthcare system, overall and sex-specific prevalence of never smoking were estimated according to sociodemographic and clinical characteristics. Adjusted prevalence ratio (aPR) and 95% confidence interval (CI) were also estimated using modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In line with the available evidence ( 10 , 11 ), Banks et al ( 1 ) found that women diagnosed of lung cancer are more likely to be never-smokers in comparison to men. It is also noteworthy that this difference is maintained in almost all age groups, races/ethnicities and histological types of lung cancer, as seen in other investigation ( 7 ).…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…In line with the available evidence ( 10 , 11 ), Banks et al ( 1 ) found that women diagnosed of lung cancer are more likely to be never-smokers in comparison to men. It is also noteworthy that this difference is maintained in almost all age groups, races/ethnicities and histological types of lung cancer, as seen in other investigation ( 7 ).…”
mentioning
confidence: 70%
“…Banks et al ( 1 ) concluded in their study with important sociodemographic and clinical disparities in subjects diagnosed with lung cancer depending on their smoking status. Banks et al found that never-smokers diagnosed with lung cancer were more frequently women, Asian/Pacific Islanders and Hispanic patients and had adenocarcinoma or carcinoid tumours.…”
mentioning
confidence: 94%
See 3 more Smart Citations